2013
DOI: 10.1002/jctb.4216
|View full text |Cite
|
Sign up to set email alerts
|

A kinetic analysis of catalytic production of oxygen in catalase‐containing liposome dispersions for controlled transfer of oxygen in a bioreactor

Abstract: BACKGROUND: Biochemical oxidation reactions require oxygen to be supplied by dispersed bubbles. Drawbacks of the gas-liquid system are enzyme denaturation and low oxygen utilization efficiency. Therefore, oxygen production through the decomposition of H 2 O 2 is useful for controlled oxygen transfer in bioreactors. RESULTS:Catalase-containing liposomes (CALs) were prepared in 50 mmol L -1 Tris/0.1 mol L -1 NaCl buffer (pH 7.4) and the kinetic model was developed for the oxygen production by CAL-catalyzed decom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…The oxygen replenishment performed by catalase is described in several works. 33,34 In order to demonstrate this effect in our system, we measured the displaced gas volume when catalase/GOX decomposes 50 mM H 2 O 2 in the presence and absence of 300 mM of glucose. The displaced volume was 3.7 times higher when glucose was added to the system (0.14 and 0.56 mL with or without glucose, respectively), thus demonstrating higher oxygen production.…”
Section: Resultsmentioning
confidence: 99%
“…The oxygen replenishment performed by catalase is described in several works. 33,34 In order to demonstrate this effect in our system, we measured the displaced gas volume when catalase/GOX decomposes 50 mM H 2 O 2 in the presence and absence of 300 mM of glucose. The displaced volume was 3.7 times higher when glucose was added to the system (0.14 and 0.56 mL with or without glucose, respectively), thus demonstrating higher oxygen production.…”
Section: Resultsmentioning
confidence: 99%
“…The HRPC molecules cannot cross the membrane due to their large size, and ABTS 2− molecules cannot move from the external bulk solution into the interior of the vesicles due to their negative charge. On the contrary, H 2 O 2 , being small and uncharged, can easily permeate across fluid phospholipid bilayers [ 47 ]. The release of HRPC from the LUVs and/or the uptake of ABTS 2− by the LUVs after peptide addition can be conveniently monitored by UV-vis spectrophotometry as the HRPC-catalysed oxidation of ABTS 2− to ABTS •− results in increased absorbance (see Figure 6 for a schematic representation of the permeability assay).…”
Section: Resultsmentioning
confidence: 99%
“…Chapman et al () suggested that one might eliminate the requirement for gas–liquid transport through the in situ generation of O 2 from H 2 O 2 . A number of studies before Chapman et al () have elaborated on the concept (Bolivar, Schelch, et al, ; Schneider, Dorscheid, Witte, Giffhorn, & Heinzle, ; Van Hecke et al, ; Yoshimoto & Higa, ). To overcome the limit of OTR at ambient pressure (for use at high pressure, see Figures and ), the H 2 O 2 ‐based oxygenation would have to be performed strictly under conditions of rate‐limiting formation of O 2 (Bolivar, Schelch, et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Catalyst productivity b (g product/g enzyme) STY (g/[L·hr]) X = 0.1 X = 0.9 X = 0.1 X = 0.9 X = 0.1 X = 0.9 (2018) have elaborated on the concept (Bolivar, Schelch, et al, 2016;Schneider, Dorscheid, Witte, Giffhorn, & Heinzle, 2012;Van Hecke et al, 2009;Yoshimoto & Higa, 2014). To overcome the limit of OTR at ambient pressure (for use at high pressure, see Figures 2 and 3), the H 2 O 2 -based oxygenation would have to be performed strictly under conditions of rate-limiting formation of O 2 (Bolivar, Schelch, et al, 2016).…”
Section: Reaction Kinetic Analysismentioning
confidence: 99%